Equal Expansion of Endogenous Transplant-Specific Regulatory T Cell and Recruitment Into the Allograft During Rejection and Tolerance - Young, James S.; Yin, Dengping; Vannier, Augustin Georges Louis; Alegre, Maria-Luisa; Chong, Anita S. (Frontiers in Immunology, 2018)
Despite numerous advances in the definition of a role for Tregs in facilitating experimental transplantation tolerance, and ongoing clinical trials for Treg-based therapies, critical issues related to the optimum dosage, antigen-specificity and Treg-friendly adjunct immunosuppressants remain incompletely resolved. In this study, we used a tractable approach of MHC tetramers and flow cytometry to define the fate of conventional (Tconvs) and regulatory (Tregs) CD4+ T cells that recognize donor 2W antigens presented by I-Ab on donor and recipient antigen presenting cells (APC) in a mouse cardiac allograft transplant model. Our study shows that these endogenous, donor-reactive Tregs comparably accumulate in the spleens of recipients undergoing acute rejection or exhibiting costimulation blockade-induced tolerance. Importantly, this expansion was not detected when analyzing bulk splenic Tregs. Systemically, the distinguishing feature between tolerance and rejection was the inhibition of donor-reactive conventional T cell (Tconv) expansion in tolerance, translating into increased percentages of splenic FoxP3+ Tregs within the 2W:I-Ab CD4+ T cell subset compared to rejection (~35% vs <5% in tolerance vs rejection). We further observed that continuous administration of rapamycin, cyclosporine A (CsA) or CTLA4-Ig did not facilitate donor-specific Treg expansion, while all three drugs inhibited Tconv expansion. Finally, donor-specific Tregs accumulated comparably in rejecting and tolerant allografts, whereas tolerant grafts harbored <10% of the donor-specific Tconv numbers observed in rejecting allografts. Thus, ~80% of 2W:I-Ab CD4+ T cells in tolerant allografts expressed FoxP3+ compared to ≤10% in rejecting allografts. A similar, albeit lesser, enrichment was observed with bulk graft-infiltrating CD4+ cells, where ~30% were FoxP3+ in tolerant allografts, compared to ≤10% in rejecting allografts. Finally, we assessed that the phenotype of 2W:I-Ab Tregs and observed that the percentages of cells expressing neuropilin-1 and CD73 were significantly higher in tolerance compared to rejection, suggesting that these Tregs may be functionally distinct. Collectively, the analysis of donor-reactive, but not of bulk, Tconvs and Tregs reveal a systemic signature of tolerance that is stable and congruent with the signature within tolerant allografts. Our data also underscore the importance of limiting Tconv expansion for high donor-specific Tregs:Tconv ratios to be successfully attained in transplantation tolerance.